CONTEXT IS KEY: THE IMPACT OF CONTEXTUAL CLUES ON ACEHNESE PROVERB COMPREHENSION - Ibnu Hajar (Universitas Warmadewa, 2026)
This study attempted to investigate the role of context in interpreting Acehnese proverbs. It was conducted on forty-two Acehnese students studying at Bumi Persada University in Lhokseumawe, Indonesia. Data were gathered via online questionnaires with multiple-choice questions. Respondents were invited to answer the questions in two sessions. Respondents' scores in the first session represent their ability to interpret the meaning of proverbs without context, whereas respondents' scores in the second session describe their ability to interpret the meaning of proverbs using context. Their scores from both sessions were compared to see if there were any gains between them. The result of the data analysis demonstrated that the average score of respondents answering questions about Acehnese proverbs with context increased when compared to the average score of respondents answering the same questions without context. This increase in score demonstrates the need for context when interpreting Acehnese proverbs.